Inflation, Invesment, And Economic Growth - Agnes Soukotta; Dian Ariani; Pandu Adi Cakranegara; PA. Andiena Nindya Putri; Irwan Moridu (Pusat Riset dan Inovasi Nasional, 2023)
Economic growth is one of the key indicators used to analyze a country's economic development. A country with consistently increasing economic growth year after year will enhance its development. The purpose of this study is to examine the impact of investment, inflation, and public consumption on economic growth in Bandung. This study makes use of secondary data, namely time series data from 2012 to 2022. Multiple linear regression analysis with SPSS 25 software was employed as an analytical method in this study. The study's findings suggest that, in Bandung, partially investment has little effect on economic growth, inflation has a negative and large effect on economic growth, and public consumption has a significant positive effect on economic growth.